Decreased expression of suprabasin induces aberrant differentiation and apoptosis of epidermal keratinocytes: Possible role for atopic dermatitis. Issue 3 (September 2019) - Aoshima, Masahiro; Phadungsaksawasdi, Pawit; Nakazawa, Shinsuke; Iwasaki, Manami; Sakabe, Jun-ichi; Umayahara, Takatsune; Yatagai, Tsuyoshi; Ikeya, Shigeki; Shimauchi, Takatoshi; Tokura, Yoshiki
Abstract: Background: Suprabasin (SBSN), a secreted protein, is expressed in various epithelial tissues. The role of SBSN in epidermal differentiation and atopic dermatitis (AD) pathology remains largely unknown. Objective: To evaluate the effects of SBSN on epidermal keratinocytes and its role in AD. Methods: We examined the SBSN expression levels in the stratum corneum and the epidermis by proteome analysis and immunohistochemistry, respectively. The serum SBSN concentration was measured by ELISA. These values were compared between AD and healthy control. Morphological changes in the epidermis were investigated in SBSN-knockdown three-dimensional human living skin equivalent (LSE) model with or without IL-4/IL-13. Results: Epidermal SBSN expression was decreased in AD lesional skin compared to healthy skin, as assessed by the stratum corneum proteome analysis and immunohistochemistry. The SBSN serum levels were significantly lower in AD patients than in normal subjects (P <0.05). The SBSN-deficient LSE exhibited compact stratum corneum, immature stratum granulosum, and increased keratinocyte apoptosis. Th2 cytokines, IL-4 and IL-13, did not affect SBSN expression in LSE. There were no differentiation-associated makers that were affected by the SBSN knockdown. SBSN deficiency-induced apoptosis of keratinocytes was exaggerated by IL-4/IL-13, and accordingly, the addition of recombinant SBSN induced significant keratinocyte proliferation (P <0.05). Conclusion: Our data demonstrated that SBSN regulates normal epidermal barrier. Th2 cytokines unaffect SBSN expression in keratinocytes, but promote SBSN deficiency-induced apoptosis. It is suggested that SBSN has an anti-apoptotic activity, and its deficiency is involved in the pathogenesis of AD.